The Measurement of Extensive Reading and Reading Strategy among EFL Learners - Masrul, Masrul; Wicaksono, Bayu Hendro (Universitas Negeri Medan, 2023)
This study investigated the correlation between variables affecting extensive reading measured through six indicators: Content, Communicative achievement, Organization, Language use, Vocabulary and Mechanics. This study also examined the correlation between variables in the reading strategy category through four indicators: Description of appearance, Psychology, Expression and Action. There were 100 participants consisting of 40 males and 60 females from the State University of Yogyakarta in this study. This correlational study identified close associations between independent and dependent variables. ANOVA and Independent T Test were also performed. The results of this study showed that Content indicator shared fairly strong correlations with Organization, Language use, Vocabulary, and mechanics. However, it did not have share significant correlation with the Communicative achievement indicator. The Communicative achievement indicator strongly correlated to Organization, Language use, Vocabulary, and mechanics. Furthermore, Organization strongly correlated with Language use and Vocabulary indicator, while Description of appearance strongly correlated with psychology, expression, and action. Psychology shared fairly strong correlation with the Expression indicator, yet it did not correlate to the Action, yet Action and Expression shared strong relationship.